Update of mortality and cancer incidence in the Australian petroleum industry cohort. Issue 7 (12th May 2006) - Gun, R T; Pratt, N; Ryan, P; Roder, D
Abstract : Objectives: To update the analysis of the cohort mortality and cancer incidence study of employees in the Australian petroleum industry. Methods: Employees of Australian Institute of Petroleum member companies were enrolled in the cohort in four industry-wide surveys between 1981 and 1999. Mortality of 16 547 males and 1356 females was determined up to 31 December 2001 and cancer incidence to 31 December 2000. Cause specific mortality and cancer incidence were compared with those of the Australian population by means of standardised mortality ratios (SMRs) and standardised incidence ratios (SIRs). Associations between increased incidence of specific cancers and employment in the petroleum industry were tested by trends according to period of first employment, duration of employment, latency, and hydrocarbon exposure, adjusting for personal smoking history where appropriate. Results: There was a significant elevation of the incidence of mesothelioma (SIR 1.77, 95% CI 1.05 to 2.79), melanoma (SIR 1.37, 95% CI 1.19 to 1.58), and prostate cancer (SIR 1.18, 95% CI 1.04 to 1.34). The SIRs of all leukaemias and of acute non-lymphocytic leukaemia (ANLL) were not significantly different from unity, but all 11 ANLL cases were clustered in the middle to high hydrocarbon exposure categories. Tanker drivers had a significantly elevated incidence of kidney cancer (12 cases v 5.84 expected, SIR 2.05, 95% CI 1.06 to 3.59). Lung cancer incidence was significantly reduced (SIR 0.69, 95% CI 0.57 to 0.83) Conclusions: Most cases of mesothelioma are probably related to past exposure to asbestos in refineries. No occupational cause has been identified for the excess of melanoma, or prostatic or bladder cancer. The possibility of a causal relationship between cancer of the kidney and hydrocarbon exposure warrants further study. It is uncertain whether benzene exposures, particularly past levels of exposure, have been high enough to cause ANLL.